Expert Network Time Protocol: An Experience in Time with NTP - Rybaczyk, Peter (Apress, 2012)
Time permeates every facet of modern-day computing and networking. It is also an integral element of everyday living. And it’s a given that most networking professionals have at one time or another encountered and/or configured NTP, even if without fully understanding the science of accurate and synchronized timekeeping behind it. You do not need NTP at all if you are satisfied with networks where every internal and external clock ticks to its own rhythm, keeping track of time independent of all the other clocks. You can also navigate throughout your entire networking career with a limited understanding of NTP when accurate timekeeping is a nicety but hardly a necessity on the networks you support.